Impact of Aluminum Industry Development on Public Welfare and State Defense - Al-Fadel Arman Rizzy; Edy Sulistyadi; Khaerudin , Khaerudin; Muhamad Asvial; Rudy AG Gultom; Aggria Purja; Afpriyanto, Afpriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research focuses on the impact of the development of the aluminum industry on the welfare of society and national security in Indonesia. As a strategic sector, the aluminum industry plays a central role in economic growth and national defense. The research aims to identify complex social impacts and provide detailed policy recommendations. The research method used is Systematic Literature Review (SLR), which collects and analyzes relevant literature between 2014 and 2024. The results show positive growth in the production and employment of the aluminum industry, with the adoption of current technology improving worker qualifications. However, the research also reveals several challenges, including job displacement, uncontrolled urban growth, and environmental impact. The role of aluminum in national defense indicates dependence on key resources, requiring diversification strategies and supply security. Policy implications emphasize the need for equitable distribution of benefits, sustainable defense strategies, and a balance between defense needs and societal welfare. The conclusion of this research is that the aluminum industry in Indonesia, despite its positive impact on the economy and defense, also poses complex challenges. Collaboration between the government, industry, and society is key to managing these impacts, with wise policies to create a balanced, sustainable environment that supports national development. This research contributes to the social sciences literature and serves as a basis for wiser policies in managing the social and security impacts of the development of the aluminum industry in Indonesia.